Theoretical study on the structural evolution and hydrogen storage in NbHn (n = 2–15) clusters. (13th May 2021) - Zhou, Wenli; Jin, Siyu; Dai, Wei; Lyon, Jonathan T.; Lu, Cheng
Abstract: Niobium hydrides are attractive superconductors. Exploring the formation process of niobium hydrides is essential to elucidate the mechanism of superconductivity. One of the key issues is to clarify the atomic stacking patterns of Nb and H atoms, i.e., the structural evolution of Nb–H clusters. Here, the low-energy structural isomers of NbH n ( n  = 2–15) clusters are determined using the CALYPSO method combined with density functional theory calculations. Geometries were fully optimized at the B3LYP/LANL2DZ/6–311++G(d) level of theory to determine global minimum structures for each size. The results indicate that NbH13 is the most stable cluster in this size range. The 4 d atomic orbital of Nb and the hydrogen 1 s atomic orbital participate largely to the internal binding of the NbH13 cluster. They hydrogen storage density and adsorption energy of this cluster are calculated to be 12.4 wt% and 2.58 eV, respectively. The high hydrogen storage density, suitable hydrogen adsorption energy, and high stability of NbH13 shows promise as a hydrogen storage material. These results provide fundamental information for further design of metal hydrogen storage materials. Highlights: The ground state and low-energy state isomers of NbH n ( n  = 2–15) clusters are determined using CALYPSO and DFT calculations. The NbH13 cluster is more stable than the adjacent isomers with high HOMO-LUMO gap of 5.27 eV. The NbH13 cluster is potential carrier of hydrogen storage with high hydrogen storage capacity of 12.4 wt%. The dehydrogenation process of NbH n ( n  = 2–15) clusters is found to be occurred at cluster size of n  = 14.